Pengaruh Suplementasi Fe dan Vitamin C terhadap Hemoglobin dan Indeks Eritrosit Remaja Putri - Endang Sri Wahyuni (Jurnal Kesehatan, 2021)
Teenager girls are at risk of suffering from iron nutritional anemia. Anemic teenage girls also have less vitamin C intake. Anemia has an impact on learning achievement, ease of infection and impact when pregnant in the future. The study aimed to find out the effect of giving Fe and vitamin C tablets. The research design was a one-group pre-post test, using 41 Health Analyst female students from Tanjungkarang Health Polytechnic, which were determined by random sampling. Blood added tablets containing 60mg Fe, 400mcg folate, and 500mg vitamin C tablets were given once/week for 17 days (3 tablets). Hb levels were measured before and after supplementation using a digital analyzer MINDRAY BC-3600. Data collection was conducted from August-September 2020. The proportion of Hb <12mg/dl decreased from 20 (48,78%) at before to 16 (39,02%) subject after supplementation. The mean Hb level before supplementation was 12,15mg/dl, MCV 80,11fL, MCH 25,85 lpg and MCHC 32,22% and after supplementation, the mean of Hb was 12,05mg/dl, MCV 79,83 MCH 26,45, and MCHC 33,07.  The results of statistic test showed that supplementation had a significant effect on Hb levels (p-value=0,000)  MCV (p-value=0,000), MCH (p-value=0,000), and MCHC (p-value=0,000). Supplementation can reduce the proportion of anemia and improve the erythrocyte index. Another research with longer duration time and nutritional education combination is needed to confirm the increasing of  nutrient intake (Fe, vitamin C) and Hb level.